Pengaruh suhu pengeringan terhadap karakter fisikokimia dan aktivitas antioksidan tisane daun rosella (Hibiscus sabdariffa L.) - Fiddini Nurul Hasri; Misril Fuadi; Nur Izalin Binti Mohamad Zahari; Muhammad Shafiq Bin Johari; Norra Ismail; Norhartini Abdul Samad (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2026)
Roselle leaf tisane is the name for an herbal tea made from dried roselle leaves. Tisanes are popular for their aroma, antioxidant content, and therapeutic properties. Roselle leaves are known to be a source of antioxidants, flavonoids, and phenolic compounds, which contribute to their health benefits. This study aimed to investigate the effect of drying temperature on the physicochemical characteristics, antioxidant activity, and sensory acceptance of Roselle (Hibiscus sabdariffa L.) tisane. Roselle leaves were dried at 40°C, 50°C, and 60°C, and the resulting powders were analyzed for moisture content, water activity, color, total phenolic content (TPC), FRAP, DPPH, TEAC, total flavonoid content (TFC), pH, and sensory properties of the infusion at 60°C. Results showed that moisture and water activity decreased with increasing drying temperature, reaching the lowest values at 60°C. Antioxidant activities, including TPC, FRAP, DPPH, TEAC, and TFC, significantly increased at higher drying temperatures. The infusion pH slightly decreased with temperature, while color and overall sensory acceptance did not show significant differences. These findings indicate that drying at 50–60°C can enhance the bioactive compounds and antioxidant activity of Roselle leaves without compromising sensory quality. This study provides valuable insights for optimizing Roselle processing as a functional beverage with high antioxidant potential.